I have a sister--my sister is deaf - Peterson, Jeanne Whitehouse; Ray, Deborah Kogan (New York : Harper & Row, 1977)
A young girl describes how her deaf sister experiences everyday things.
Keywords: Deaf children; Deaf children; Sisters; Deaf; Sisters